Parameters of the Blood Oxidant/Antioxidant System in Elderly Patients with Acute Poisoning - A. Yu. Simonova; K. K. Ilyashenko; E. V. Klychnikova; A. K. Evseev; M. M. Potskhveriya; M. V. Belova; E. V. Tazina; A. S. Shabanov; A. N. Kuzovlev (Общая реаниматология)
The aim of the study was to assess the oxidant/antioxidant status in elderly patients in the early period of acute poisoning by psychotropic drugs or corrosive substances.Material and methods. An open prospective observational study with retrospective control was conducted in 80 patients (age ≥ 60 years) with acute poisoning, of which 49 patients aged 72.1±9.55 years had psychotropic drug poisoning (PDP) and 31 subjects aged 73.0±10.3 years had corrosive substance poisoning (CSP). Patients with mild poisoning were excluded from the study. The control group consisted of 39 volunteers aged 68.3±6.3 years. Total antioxidant status (TAS), blood levels of malondialdehyde (MDA), stable nitric oxide metabolites (nitrite/nitrate, NOx), and oxidative stress index (MDA/TAS) were measured on days 1, 3 and 5 after hospital admission.Results. When analyzing the changes in the parameters of the oxidant/antioxidant system, we observed lower values of the studied parameters in patients with both PDP and CSP compared to the control group. In patients with PDP, several parameters were reduced: MDA by 1.2 times on days 1 and 3 (P=0.002; P=0.008, respectively), NOx by 1.7 times (P<0.001) at all stages of the study, MDA/TAS by 2.4–2.9 times (P<0.001). In patients with CSP, MDA level decreased by 1.1–1.2 times at all study timepoints (P=0.003; P=0.010; P=0.046, respectively), NOx dropped 1.4–1.6-fold (P=0.012; P=0.004; P=0.023, respectively), and MDA/TAS decreased by 2.3–2.4 times (P<0.001). While comparing patients with favorable and fatal outcome, we found that in survived patients an increase of MDA/TAS along with growing NOx level was seen by day 5 with no signiﬁcant changes of MDA and TAS, while in non-survivors MDA/TAS dropped continuously due to progressive fall of NOx level, reaching values 2.8–2.9 times (P<0.001) lower than those of the controls.Conclusion. In elderly patients with acute poisonings due to psychotropic drugs or corrosive substances, an inadequate response of the oxidant/antioxidant system occurs manifesting as a reduced blood level of peroxidation products with simultaneous normal or slightly decreased concentration of antioxidant protection system components. Thus, the oxidative stress develops, which contributes to the death of the patients.